Factors That Influence Increased Revenue: Baggage Drop Services, Determining Flight Time Slots, and Selection of Tenants - Yudistiawan, Yudistiawan; Permana, Verry Rizki; Simarmata, Juliater (Dinasti Publisher, 2024)
Article on factors that influence increasing revenue: baggage drop service, determining flight time slots, and tenant selection within the scope of marketing management science. This article aims to create hypotheses regarding the relationship between factors, which can then be used for further research in the field of marketing management. The research method used in this research is descriptive qualitative. The data used in this research comes from previous research which is still relevant to the current investigation. Data was collected from leading academic online platforms, including Publish or Perish, Google Scholar, digital reference books, and Sprott journals. The results of this literature research include: 1) Baggage drop services have an effect on increasing revenue; 2) Determining the flight slot time has an effect on increasing revenue; and 3) Tenant selection has an effect on increasing revenue.